2016
DOI: 10.1128/jb.00965-15
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics of Phage and Bacteria in Spatially Structured Habitats Using Phage λ and Escherichia coli

Abstract: Bacteria living in physically structured habitats are exposed heterogeneously to both resources and different types of phages. While there have been numerous experimental approaches to examine spatially distributed bacteria exposed to phages, there is little theory to guide the design of these experiments, interpret their results, or expand the inferences drawn to a broader ecological and evolutionary context. Plaque formation provides a window into understanding phage-bacterium interactions in physically stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
68
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 64 publications
3
68
0
Order By: Relevance
“…It must be noted that high rates of adsorption may not necessarily lead to all bacteriophages completing their infection cycle. Mitarai et al (2016) reported that plaque morphology can be affected by the nutritional state of the host bacterial cell, and the number of bacteriophages that can infect them. This is important, as the nutritional and metabolic state of bacterial cells within biofilms will be different to those in planktonic culture, as well as differences existing between early stage and mature biofilm-dwelling cells.…”
Section: Discussionmentioning
confidence: 99%
“…It must be noted that high rates of adsorption may not necessarily lead to all bacteriophages completing their infection cycle. Mitarai et al (2016) reported that plaque morphology can be affected by the nutritional state of the host bacterial cell, and the number of bacteriophages that can infect them. This is important, as the nutritional and metabolic state of bacterial cells within biofilms will be different to those in planktonic culture, as well as differences existing between early stage and mature biofilm-dwelling cells.…”
Section: Discussionmentioning
confidence: 99%
“…We use the Lotka-Volterra type ordinary differential equations to model the population dynamics of the system, which has been used to describe temperate phage and bacteria population dynamics [18,23,29,26]. To extend the model 80 to the pirate-helper phage system described in Fig.…”
Section: Growth In a Well-mixed Culturementioning
confidence: 99%
“…For the well-mixed case, we use the Lotka-Volterra type equations. For the plaque simulation, we let bacteria grow locally while 70 let phage and nutrient diffuse, describing the system using a reaction-diffusion type model [19,26]. In both cases, we consider time scale of an overnight, where effect of the induction and the mutation are negligible.…”
Section: Introductionmentioning
confidence: 99%
“…A number of theoretical models [5], [10], [11], [12] have 22 been proposed to explain the observed experimental trends. Although these 23 models do provide a possible understanding of the system, they have their own 24 limitations. Avlund et al [10] provide a game-theoretical model to explain the 25 decision between lysogeny and lysis, the parameters for which are similar to 26 those used in the current work.…”
mentioning
confidence: 99%
“…15, 2018; -shown by the red curve with an extremely small error area. Classically, en-172 vironments have been assumed to be good [11], [24], thus missing out on the 173 variation caused by changes in the values of the parameters in bad environments. 174 It is interesting to note that as the environment becomes worse for phages, the 175 lysogenic propensity at a given M oI decreases.…”
mentioning
confidence: 99%